The Qur'anic Strategy In Overcoming Islamophobia Using Rahmatan lil 'Alamîn Approach - Yusron, M Agus; Febriani, Nur Arfiyah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
Islamophobia is a worldwide issue that impacts Muslims, particularly in countries where they are a minority. Therefore, it is crucial to prevent or reduce various forms of Islamophobia. This research aims to re-establish the loving essence of Islam to foster a genuine affection for the faith. This, in turn, will promote peace amidst diversity, rather than the proliferation of Islamophobia or other types of religious intolerance. This research employs a descriptive qualitative method with conceptual thematic technique. It involves examining Qur’anic verses that specifically mention the contestation of Islamophobia, furthermore, analyzing them to determine how to prevent it. By portraying the face of Islam, using the frame of rahmatan lil 'alamîn, which is in accordance with the Islamic identity, the research findings indicate that the fear of non-Muslims can be eradicated. Islamic precepts of tolerance for religious diversity, treating everyone with kindness and justice, and presenting Islam as a religion of rahmatan lil 'alamin are all things that must be demonstrated. This research underscores that the Qur'an does not promote religious phobia; rather, its teachings are rich in universal values that resonate across different contexts and eras.